Sertifikasi Dai MUI dan ADDAI sebagai Produk Dakwah: Strategi Distribusi, Harga, dan Dampaknya terhadap Ekonomi Umat - Wahidin; Muhamad Zen; Fatmawati (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
Certification of MUI and ADDAI Dai as a da'wah product, which includes distribution strategies, pricing, and its impact on the people's economy. Certification of da'wah is an effort to improve the quality and competence of da'wah in Indonesia, which is expected to produce quality and broad-minded preachers. To disseminate information about this certification program, MUI and ADDAI utilize various communication channels, including social media. This approach aims to reach all da'wah in Indonesia effectively and efficiently. Although this certification is not profit-oriented, setting a reasonable fee to participate in the certification program is needed in order to support the sustainability of the program and provide access to more da'wah. By increasing the quality of da'wah through certification, it is hoped that there will be a positive impact on the people's economy. Quality preachers can provide a better understanding of the principles of Islamic economics to the community, thus encouraging participation in sharia-compliant economic activities. Through this research, it is hoped that new ways can be found to optimize the da'wah certification program in order to improve the quality of da'wah and its contribution to the people's economy.